Village Roles in Tax Compliance: Suboptimal Mobilization and Limited Facilitation: Peran Desa dalam Kepatuhan Pajak: Mobilisasi yang Kurang Optimal dan Fasilitasi yang Terbatas - Arydianti, Fadila Putri; Mursyidah, Lailu (Indonesian Journal of Public Policy Review, 2025)
General Background Land and Building Tax (PBB) is a primary revenue source vital for local development, making taxpayer compliance essential for municipal financing. Specific Background Despite the strategic importance of PBB, compliance rates in Sidoarjo Regency remain variable , particularly in Keper Village, where PBB realization consistently hovers between 50% to 60%. Knowledge Gap This persistent underperformance suggests a suboptimal role of the local village government in mobilizing and motivating its taxpayers. Aims This qualitative descriptive study aims to analyze and describe the implementation of the Keper Village Government's role based on Bintoro Tjokroamidjojo’s (2000) framework: motivator, facilitator, and mobilizer. Results Findings indicate the motivator role is suboptimal due to the lack of formal socialization and absence of legal sanctions. The facilitator role is constrained as payment services at the village hall are strictly limited to working days and hours. Although the mobilizer role employs direct SPPT distribution and social media, these efforts have not succeeded in raising public awareness or collection rates. Novelty The study provides an indicator-based diagnostic of local governance deficits that impede tax compliance in rural settings. Implications The findings imply that a systematic shift towards mandatory socialization, clear incentive structures, and flexible service facilitation is required to boost tax collection and support local development. Highlights: Lack of formal socialization weakens the village government's role as a tax motivator. PBB payment services at the village hall are restricted to working days and business hours. Despite various mobilization efforts, public awareness and tax collection rates remain consistently low. Keywords: Role of Village Government, Community Awareness, Land and Building Tax, Tax Compliance, Local Governance